Biochemical characterization and selective inhibition of β‐carotene cis–trans isomerase D27 and carotenoid cleavage dioxygenase CCD8 on the strigolactone biosynthetic pathway. (31st August 2015) - Harrison, Peter J.; Newgas, Sophie A.; Descombes, Flora; Shepherd, Sarah A.; Thompson, Andrew J.; Bugg, Timothy D. H.
<x xml:space="preserve">Abstract</x> The first three enzymatic steps of the strigolactone biosynthetic pathway catalysed by β‐carotene cis–trans isomerase Dwarf27 (D27) from Oryza sativa and carotenoid cleavage dioxygenases CCD7 and CCD8 from Arabidopsis thaliana have been reconstituted in vitro, and kinetic assays have been developed for each enzyme, in order to develop selective enzyme inhibitors. Recombinant OsD27 shows a UV‐visible λmax at 422 nm and is inactivated by silver(I) acetate, consistent with the presence of an iron–sulfur cluster that is used in catalysis. OsD27 and AtCCD7 are not inhibited by hydroxamic acids that cause shoot branching in planta, but OsD27 is partially inhibited by terpene‐like hydroxamic acids. The reaction catalysed by AtCCD8 is shown to be a two‐step kinetic mechanism using pre‐steady‐state kinetic analysis. Kinetic evidence is presented for acid–base catalysis in the CCD8 catalytic cycle and the existence of an essential cysteine residue in the CCD8 active site. AtCCD8 is inhibited in a time‐dependent fashion by hydroxamic acids D2, D4, D5 and D6 (> 95% inhibition at 100 μm) that cause a shoot branching phenotype in A. thaliana, and selective inhibition of CCD8 is observed using hydroxamic acids D13H and D15 (82%, 71% inhibition at 10 μm). The enzyme inhibition data imply that the biochemical basis of the shoot branching phenotype is due to inhibition of CCD8.